Influence of doxorubicin treatment on heme metabolism in cardiomyoblasts: An in vitro study - Gatto, Mariana [UNESP] (2021)
Departamento de Clínica Médica Faculdade de Medicina de Botucatu Universidade Estadual Paulista-Unesp